A Monocular Projector-Camera System Using Modular Architecture - Yamamoto, Kenta (IEEE transactions on visualization and computer graphics, 2023)
This paper presents a monocular projector-camera (procam) system using modular architecture based on relay optics. Conventional coaxial procam systems cannot support (1) online changes to lens settings (zoom and focus) and (2) wide-angle projection mapping. We develop design guidelines for a proposed procam system that would solve these restrictions and address the proposed system's unique technical issue of crosstalk between the camera and projector pixels. We conducted experiments using prototypes to validate the feasibility of the proposed framework. First, we confirmed that the proposed crosstalk reduction technique worked well. Second, we found our technique could achieve correct alignment of a projected image onto a moving surface while changing the zoom and focus of the objective lens. The monocular procam system also achieved radiometric compensation where a surface texture was visually concealed by pixel-wise control of a projection color based on the captured results of offline color pattern projections. Finally, we demonstrated the high expandability of our modular architecture, through the creation of a high dynamic range projection